Mode of action of triflumezopyrim: A novel mesoionic insecticide which inhibits the nicotinic acetylcholine receptor. (July 2016) - Cordova, Daniel; Benner, Eric A.; Schroeder, Mark E.; Holyoke, Caleb W.; Zhang, Wenming; Pahutski, Thomas F.; Leighty, Robert M.; Vincent, Daniel R.; Hamm, Jason C.
Abstract: Triflumezopyrim, a newly commercialized molecule from DuPont Crop Protection, belongs to the novel class of mesoionic insecticides. This study characterizes the biochemical and physiological action of this novel insecticide. Using membranes from the aphid, Myzus persicae, triflumezopyrim was found to displace 3 H-imidacloprid with a Ki value of 43 nM with competitive binding results indicating that triflumezopyrim binds to the orthosteric site of the nicotinic acetylcholine receptor (nAChR). In voltage clamp studies using dissociated Periplaneta americana neurons, triflumezopyrim inhibits nAChR currents with an IC50 of 0.6 nM. Activation of nAChR currents was minimal and required concentrations ≥100 μM. Xenopus oocytes expressing chimeric nAChRs ( Drosophila α2/chick β2) showed similar inhibitory effects from triflumezopyrim. In P. americana neurons, co-application experiments with acetylcholine reveal the inhibitory action of triflumezopyrim to be rapid and prolonged in nature. Such physiological action is distinct from other insecticides in IRAC Group 4 in which the toxicological mode of action is attributed to nAChR agonism. Mesoionic insecticides act via inhibition of the orthosteric binding site of the nAChR despite previous beliefs that such action would translate to poor insect control. Triflumezopyrim is the first commercialized insecticide from this class and provides outstanding control of hoppers, including the brown planthopper, Nilaparvata lugens, which is already displaying strong resistance to neonicotinoids such as imidacloprid. Graphical abstract: Highlights: Mesoionics represent a novel class of insecticides. The mesoionic insecticide, triflumezopyrim, provides excellent hopper control. Unlike neonicotinoids, nicotinic acetylcholine receptor (nAChR) inhibition is the toxicological mode of action for triflumezopyrim.